Advancing suicide prevention in Germany, Austria and Switzerland: a qualitative study - Werdin, Sophia; Wyss, Kaspar (Frontiers in Public Health, 2024)
Introduction Suicide is a significant public health problem, impacting individuals, families and communities worldwide. Effective suicide prevention requires a comprehensive approach with diverse integrated interventions and collaboration across sectors, stakeholders and professions. This study aims to identify challenges, gaps and success factors in current suicide prevention efforts in Germany, Austria and Switzerland, providing specific recommendations for advancement. Methods We conducted online, semi-structured interviews with 36 suicide prevention experts from Germany, Austria and Switzerland, incorporating perspectives from policy, science and practice. Interviews were conducted between September 2022 and February 2023, audio-recorded, transcribed verbatim and analyzed using the Framework method. Results Despite progress in national strategies and coordinated efforts for suicide prevention, challenges such as resource scarcity, stigma and structural issues in psychiatric and psychotherapeutic care persist. The interviewees identified several areas for advancement, including developing targeted prevention measures for men and older people, strengthening collaboration across sectors, stakeholders and professions, and increasing the involvement of individuals with lived experience. While the COVID-19 pandemic has exacerbated challenges in psychiatric and psychotherapeutic care, it has concurrently strengthened interest in suicide prevention among policymakers and the media. Discussion National suicide prevention strategies play a crucial role in setting priorities, raising public awareness, and guiding action. However, since most suicide prevention efforts are still predominantly health sector-driven, a more comprehensive approach is needed to promote the involvement of all relevant actors and address suicidality as a collective societal responsibility. Tailoring prevention programs for risk groups like older people and men is important, as these populations show high suicide rates and face a lack of targeted interventions. Our study underscores the importance to continuously monitor, refine and strengthen collaborative and evidence-based suicide prevention efforts.